10 - The Challenges of Education and Development in Post-Colonial Kenya: 10.4314/ad.v28i2.22183 - Ntarangwi, Mwenda (Africa Development, 2003)
Explorations of socio-cultural realities of many African countries in the post colonial era reveal a very complex yet saddening reality. Poor infrastructure, large numbers of the local populations living below poverty lines, and contin ued civil and ethnic strife are some of the most prevalent identifiable markers of post-colonial Africa. This paper addresses the legacy of colonialism as mani fested in the educational system of Kenya in the post-colonial era. 1 argue that although Kenya is an independent country, it is overly dependent on the West for its cultural and intellectual nourishment. I critically analyse the role of edu cation in shaping a national sense of identity and as an agent for development. I show that the education system offered in Kenya needs a total overhaul in order to tap the best of its brains by recreating a new cultural orientation. Therefore, this paper examines, with examples from Kenya, the condition of post-coloniality as it relates to education and development, two concepts that are closely related in both national and individual discourses. I argue that through colonialism and post-colonialism, Kenyans have absorbed imperialist values that consequently condition them to think of'development' as the process of shedding any traces of their unique traditions and cultural practices. This has led to a situation where majority of Kenyans have become schizophrenic members of a nation-state that tries to nurture citizens who strive to be Western and yet remain Kenyan. I also argue that even after three decades of political independence, Kenya's educa tion system has not been able to tailor its content and pedagogy to the socio economic and cultural realities of its people. Instead it continues to uphold an education system that is centered around schooling rather than learning and which consequently produces a people who are incapable of fitting into their own social environments. 1 often revert to the first person to articulate my own embeddedness in that which I am critiquing.